Anesthetic management of a parturient with Ehlers-Danlos syndrome posted for elective cesarean section - Della Vella Beatrice; Luca Titi; Maria Grazia Tarsitano; Maria Luisa Borgia (Wolters Kluwer Medknow Publications, 2014)
A heterogeneous group of inherited disorders of the connective tissue, characterized by skin hyperextensibility, joint hypermobility and tissue fragility, is defined as Ehlers-Danlos syndrome (EDS). The clinical manifestations vary depending on the type of disease. This syndrome may be associated with numerous pregnancy complications, ranging from mild articular discomfort to maternal death. We report the anesthetic management and the literature review of a parturient with EDS undergoing elective cesarean section.